Synthesis, Antimicrobial Evaluation and QSAR Studies of Stearic Acid Derivatives - Tahlan, S.; Kumar, P.; Narasimhan, B. (Drug Research, 2014)
A series of Schiff bases (1–17) and esters (18–28) of stearic acid was synthesized and characterized by physicochemical as well as spectral means. The synthesized compounds were evaluated in vitro for their antimicrobial activity by tube dilution method. The antimicrobial screening results indicated that the compounds having electron releasing groups on benzylidene nucleus were found to be more active against bacterial strains and compounds having electron withdrawing groups on benzylidene nucleus were found to be more active against fungal strains. QSAR studies demonstrated that electronic parameters dipole moment (µ) and total energy (Te) were the most important descriptors in describing the antimicrobial activity of synthesized stearic acid derivatives.
Keywords: stearic acid derivatives; antibacterial; antifungal; QSAR